Growing Assets, Persistent Unemployment? A Critical Evaluation of the Role of Islamic Economics and Financial Inclusion in Indonesia - Akhwalis Shalihah Shalihah; Nabila Nur Balqis; Rensi Amalia; Risti Nur Fasana; M. Taufiqurrahman (CV. Era Digital Nusantara, 2025)
This study aims to analyze the influence of Islamic economic growth and Islamic financial inclusion on the open unemployment rate in Indonesia during the semester period from 2010 to 2024. The research uses a quantitative approach with 30 time-series observations. Data were analyzed using multiple linear regression and classical assumption tests to determine the relationship among variables. The results show that Islamic economic growth has a negative influence on unemployment, while Islamic financial inclusion has a positive influence. However, both effects are statistically insignificant, either partially or simultaneously. These findings indicate that although there are logical directional relationships, the effectiveness of Islamic economic growth and financial inclusion in reducing unemployment remains limited. Therefore, a more holistic and integrative policy approach is necessary for the Islamic economic sector to make a more substantial contribution to addressing unemployment in Indonesia.